Validation of the food allergy independent measure and the EuroPrevall food allergy quality of life questionnaire for children 8-12 years translated into Spanish - Jang, Dah-Tay; Sabido, María Pérez; Buendía, Elisa; Ibáñez, Laura; Nieto, María; Bartoll, Ester; Selva, Blanca; Uixera, Sonia; Nieto, Antonio; Mazón, Ángel (Allergologia et immunopathologia, 2022)
Different questionnaires have been developed to measure quality of life (QoL) in patients with food allergy. Our aim was to validate a Spanish translation of the Food Allergy Independent Measure (FAIM) and the EuroPrevall Food Allergy Quality of Life Questionnaire-Child Form (FAQLQ-CF) for children aged 8-12 years. Sixty children with a diagnosis of IgE-mediated allergy to food completed the questionnaires. The internal consistency was evaluated with Cronbach's alpha. The correlation of FAQLQ-CF with FAIM was assessed to test construct validity. We compared both values with the diagnosis of anaphylaxis to evaluate discriminant validity. Cronbach's alpha was in the range of 0.654-0.863 for the four domains of FAQLQ-CF and 0.779 for FAIM. There were no criteria to remove questions from the questionnaires. Significant correlations could be found between FAQLQ-CF and the number of offending foods and the impact on social life (all r > 0.33, P < 0.01), and between FAIM and anaphylaxis. The Spanish translation of FAQLQ-CF showed acceptable internal consistency, good construct validity, and capacity to discriminate patients depending on the number of foods to avoid and the impact on social life. FAIM showed good discriminant capacity for anaphylaxis.